2010
DOI: 10.1002/hyp.7539
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic evolution and total suspended solids capture of an infiltration trench

Abstract: Abstract:Stormwater best management practice (BMP) design must incorporate the expected long-term performance from both a water quantity and water quality perspective to sustainably mitigate hydrologic and water quality impacts of development. Infiltration trench structures are one of many infiltration BMPs that reduce runoff volume and capture pollutants. Research on the longevity of these structures is sparse, leading to concerns about their long-term value and impeding implementation. In the present study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 25 publications
1
37
0
Order By: Relevance
“…A study conducted by Yazdi and Scholz [10] in Edinburgh, Scotland observed 73% reduction of mean flow volume and 80% reduction of mean peak flow using infiltration systems. They can also be used for capturing dissolved pollutants [1], [11]. Life spans of these systems are around 20 years [9], [12].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Yazdi and Scholz [10] in Edinburgh, Scotland observed 73% reduction of mean flow volume and 80% reduction of mean peak flow using infiltration systems. They can also be used for capturing dissolved pollutants [1], [11]. Life spans of these systems are around 20 years [9], [12].…”
Section: Introductionmentioning
confidence: 99%
“…It is unfortunate that such monitoring is not standard, because stormwater control measures can fail for a variety of reasons. The systems can release water too rapidly due to design malfunction [12], fail to infiltrate due to clogging or reduced infiltration over time [7,9], and allow the release of chemicals of concern [13,14]. If these failures could be prevented by repair or improved designs, then the dollars spent on stormwater control would be more effective.…”
Section: Introductionmentioning
confidence: 99%
“…Instrumentation may need to be built into the initial design if weirs to focus outflow are needed or if sensors to measure soil moisture or water levels need to be buried within the SCM [9,15,17]. Long-term monitoring is conducted to evaluate potential clogging infiltration basins-a common problem [9,12,14]. In some cases, stream monitoring is implemented to evaluate the impact of SCM on catchments [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…A two-part field inspection conducted by Lindsey et al (1992) in Maryland showed that about 51% of the infiltration basins surveyed (2 to 4 years of age) exhibited excessive sedimentation, clogging, inappropriate ponding of water, reduced infiltration rates and failure, and thus needed rehabilitation. Several research studies have also reported decrease in the infiltration capability with time due to deposition of sediments from runoff in the infiltration basin (Warnaars et al, 1999;Dechesne et al, 2005;Emerson et al, 2010;Lassabatere et al, 2010;Gonzalez-Merchan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%